Public Sector Financial Management and Economic Growth Sustainability in Nigeria: 1986 to 2020 - Felicia Akujinma Anyanwu; Amalachukwu Chijindu Ananwude (Journal La Bisecoman, 2021)
The Nigerian experience with public sector finance management demonstrates fiscal irresponsibility. In Nigeria, the public sector is comprised of the Federal, State, and Local governments, as well as parastatals and organizations that provide public goods and services. Nigeria's public sector, with its diverse financing sources, plays a critical role in economic management via the creation and execution of economic policies, efficient budgeting and planning targeted at attaining domestic and external balancing goals. The purpose of this research was to determine the influence of public sector financial management on the sustainability of economic development in Nigeria. The research examined the influence on real gross domestic product of total federally collected income and total government spending. The Autoregressive Distributive Lag (ARDL) technique was used to analyze data spanning the years 1986 to 2020. To begin, the findings indicate that there is no long-run association between public sector financial management and the sustainability of economic development in Nigeria. Second, overall federal revenue was shown to have a positive association with real gross domestic product. Thirdly, public sector financial management has no discernible influence on the sustainability of economic development in Nigeria. This report recommends that the ideal of sound public sector financial management be embraced in order to strengthen the sustainability of economic development in Nigeria via an effective, efficient, and transparent public account management system.